Longitudinally extensive transverse myelitis and Hepatitis C—a case report and literature review. Issue 8 (15th August 2021) - Adil, Mohammad; Jensen‐Fangel, Søren; Gammelgaard, Lise; Petersen, Thor
Abstract: Tractopathy lesions in the spinal cord associated with HCV infection, which normalized on MRI after antiviral treatment, are described. These specific MRI findings can be used in the diagnosis and treatment of secondary causes of transverse myelitis. Abstract : Few reports of HCV infection associated with ATM are reported, but the diagnosis is important. New treatment eliminated the virus, but deficits in the legs continued. This underlines the importance of testing and treating HCV as suggested by the WHO.